Evaluasi Ketepatan Penggunaan Obat Antihipertensi pada Ibu Hamil di Instalasi Rawat Inap Rsud Pandan Arang Boyolali Periode Januari - September Tahun 2016 - Alfalasifah, B Ikhoulfiria; , Dra.Nurul Mutmainah, M.Si., Apt (2017)
Hypertension in pregnancy is one of three causes of maternal mortality and morbidity in addiction to infection and bleeding. Maternal mortality rate in Boyolali in 2014 is amounted 14 cases or 93,05 per 100,000 live births which 6 cases of death due to hypertension during pregnancy, 1 case bleeding, 1 case of infection, and 6 cases by another cause of death. The aim of this research is to know the representation and the accuracy of the use of anti hypertensive drugs in pregnant women at RSUD Pandan Arang Boyolali in 2016. This research used the descriptive method which included in observational research (non-experimental) with retrospective data collection and sample taken by purposive sampling technique. The samples obtained were 39 pregnant women who received therapy with anti hypertensive drug. The data obtained were analyzed based on the accuracy of indication, patient accuracy, drug accuracy and dosage acuracy.Based on the Hospital Medical Standard, Hypertension Management in Pregnancy (Feto Maternal Medicine Association POGI, 2006) and Queensland Health (Hypertensive Disorders of Pregnancy) in 2013. Samples are 39 pregnant women, 11 patients (28.11%) were diagnosedwith gestational hypertension and 28 patients (71.79%) were diagnosed severe preeclampsia. Patients receiving single antihypertensive drug therapy of nifedipine were 21 patients (53.84%), methyldopa were 4 patients (10.26%), and combination therapy of nifedipine with methyldopa were 14 patients (35.90%). The result of analysis precise indication criteria were 39 patients (100%), precise patient criteria were 39 patients (100%), precise drug criteria were 37 patients (94,87%) and precise dosage criteria were 36 patients (92,31%).